Integrating Green Economy Principles within Islamic Economics: Toward a Sustainable Sharia Based Development - Moch Amdre; Novita Sari (IJED: International Journal of Economy Development Research, 2025)
Environmental degradation and climate change have become global challenges that require innovative economic approaches capable of balancing economic growth with ecological sustainability. In recent years, the concept of the green economy has emerged as an alternative development paradigm that emphasizes environmentally sustainable economic activities, efficient resource management, and social inclusiveness. At the same time, Islamic economics offers ethical and normative foundations that emphasize justice, balance, and environmental stewardship. This study aims to examine the conceptual relationship between green economy principles and Islamic economic values, as well as to explore the potential integration of green economy practices within the framework of Islamic finance and economic development. Using a qualitative literature-based approach, this research analyzes relevant academic works, policy documents, and theoretical frameworks related to sustainable development and Islamic economic thought. The findings indicate that Islamic economic principles such as maqasid al-shariah, prohibition of environmental harm, and the concept of khalifah (stewardship) are inherently aligned with the goals of the green economy. Furthermore, Islamic financial instruments such as green sukuk, waqf for environmental projects, and sustainable Islamic investment have significant potential to support environmentally responsible development. The study concludes that integrating green economy principles within Islamic economic systems can contribute to the creation of a sustainable development model that balances economic growth, environmental preservation, and social justice.